2007
DOI: 10.4314/eajsci.v1i1.40336
|View full text |Cite
|
Sign up to set email alerts
|

Eco-geographic Distribution and Microcenters of Genetic Diversity in Faba Bean (<i>Vica Faba</i> L.) and Field Pea (<i>Pisum Sativum</i> L.) Germplasm Collections from Ethiopia

Abstract: Abstract:Ethiopia is considered an important center of secondary diversity for both faba bean (Vicia faba L.) and field pea (Pisum sativum L.). However, areas of eco-geographic distribution and the microcenter of genetic diversity are not well known. Two separate trials consisting of 160 faba bean and 148 field pea accessions were conducted at Holetta and Kulumsa in 2001. Simple and alpha-lattice designs with 2 replications were used for faba bean and field pea, respectively. Cluster analysis grouped faba bean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…This is mainly attributable to gene flow between regions at different rates. Previous studies in P. sativum with morphological and molecular markers also showed the absence of correspondence between genetic distance and geographical distance [ 2 , 6 , 37 , 38 ]. Mixed clustering pattern of accessions was highlighted in the STRUCUTRE software-based population structure (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mainly attributable to gene flow between regions at different rates. Previous studies in P. sativum with morphological and molecular markers also showed the absence of correspondence between genetic distance and geographical distance [ 2 , 6 , 37 , 38 ]. Mixed clustering pattern of accessions was highlighted in the STRUCUTRE software-based population structure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 2000 pea accessions at the Ethiopian Institute of Biodiversity (EIB) which constitute a valuable resource in field pea breeding. However, only few of these accessions have been properly characterized for their genetic diversity and/or agronomic traits [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also revealed the presence of diverse and unique N2-fixing rhizobial species nodulating native legumes of Ethiopia (Aserse et al 2012(Aserse et al , 2017Wolde-meskel et al 2004Wolde-meskel et al , 2005. The country is considered one of the secondary gene centers of the cool season food legumes, such as faba bean, pea, lentil and chickpea (Raven and Polhill 1981;Keneni et al 2007;Khazaei et al 2016). The diversity of N2fixing rhizobial symbionts is expected to be higher in the gene center of the host plant than places where the host is introduced (Österman et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that the Ethiopian field pea landraces include valuable genetic diversity based on farmers' selection for advantageous traits across highly heterogeneous landscapes (Keneni et al, 2007; Singh & Singh, 2015). Although field pea was most likely domesticated in West Asia, the diversity of field pea varieties found by Vavilov and others led them to identify Ethiopia as a secondary center of diversity (Harlan, 1969; Vavilov et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although field pea was most likely domesticated in West Asia, the diversity of field pea varieties found by Vavilov and others led them to identify Ethiopia as a secondary center of diversity (Harlan, 1969;Vavilov et al, 1997). Agromorphological characterization and genetic analyses have confirmed the presence of high genetic diversity among Ethiopia's field pea landraces (Keneni et al, 2005(Keneni et al, , 2007Teshome et al, 2015). Despite this evidence of their genetic significance, the status of field pea landraces has not been monitored, nor has their contribution to farmers' livelihoods been evaluated.…”
mentioning
confidence: 99%